A NEW WAY TO TREAT DIABETIC FOOT SYNDROME - Sattarov, I.S.; Atakov, S.S.; Kasimov, U.K.; Khamdamov, B.Z.; Khamdamov, I.B.; Abdurakhmanov, F.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. In recent years, the use of cytokines and various growth factors in the treatment of chronic wounds in patients with diabetes mellitus has been of great interest. This manuscript is devoted to this particular problem, which made it possible to improve the results of treatment. Material and methods. The results of the treatment of 72 patients with type 2 diabetes mellitus with diabetic foot syndrome are presented, consisting of two groups: the main group (38 patients who, along with the standard treatment of diabetic foot syndrome, underwent local applications with a solution of the immunomodulator Superlymph according to the generally accepted scheme) and the comparison group (34 patients who used traditional treatment for this pathology). Clinical, laboratory and instrumental research methods available in clinical settings were used. Results and conclusions. A change in the local cytokine status in the form of a decrease in anti-inflammatory and an increase in pro-inflammatory cytokines is characteristic of patients with diabetic foot syndrome. The levels of cytokines of wound discharge exudate depend on the duration of diabetes mellitus, and the level of glycated haemoglobinand leukocytosis and do not depend on the form of diabetic foot syndrome. The use of Superlymph in the complex therapy of patients with diabetic foot syndrome contributes to the normalization of the immune status, which in turn ensures effective healing of ulcerative foot defects in diabetic foot syndrome.